FUNGSI KULTURAL PRONOMINA PERSONA PERTAMA DAN KEDUA DALAM BAHASA SASAK: KAJIAN LINGUISTIK ANTROPOLOGI - Nirwan; Suliadi (Universitas Warmadewa, 2022)
The focus of the research is concerned about the first and second singular personal pronouns in the Sasak language, especially, the Kuto-Kute dialect in North Lombok. This study is conducted to understand the form of the personal pronouns between the first and second sigular pronouns, to understand the use them, and to explore the cultural functions of those pronouns. The data in this study are vocabularies (first and second singular personal pronouns) and the speech collected by observation and interview methods. The result of the study shows that the Sasak people in North Lombok used the first and second person singular pronouns in basa jamaq or 'low language' and basa alus or 'high language'. The form of ku 'I' is the first personal pronoun of basa jamaq, while the form of the tiang 'I' is the first personal pronoun of basa alus. The form of diq that refers to 'you' is a second personal pronoun in basa jamaq, while the forms of epÑ 'you' and the word pelungguh 'you' are basa alus; The first and second singular personal pronouns in the basa jamaq are practiced when two equal interlocutors are communicating, while the first and second singular personal pronouns in the basa alus are practiced when communicating with non-equal interlocutors; The use of the first and second singular pronouns in basa jamaq and basa alusperform a cultural function between the function of intimacy and the function of politeness.